Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1978
DOI: 10.1111/j.1600-0536.1978.tb03850.x
|View full text |Cite
|
Sign up to set email alerts
|

Coolant oil dermatitis due to ethylenediamine

Abstract: Two outbreaks of hand dermatitis in light engineering works are reported. In both cases a number of workers shown to be allergic to soluble coolant oils were found to be allergic to ethylenediamine, which had either been incorporated into the oil or had been added to it later.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 10 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…Ethylene diamine has been used as a stabilizer in topical steroid creams , but is no longer used for this purpose in Sweden. Occupational cases of ethylenediamine contact allergy have been reported among workers handling epoxy systems, in which ethylenediamine and related amines are used as curing agents , and in workers exposed to ethylenediamine‐containing coolant oils and synthetic coolants . Furthermore, allergic reactions to ethylenediamine have been reported in healthcare workers handling theophylline and aminophylline .…”
Section: Discussionmentioning
confidence: 99%
“…Ethylene diamine has been used as a stabilizer in topical steroid creams , but is no longer used for this purpose in Sweden. Occupational cases of ethylenediamine contact allergy have been reported among workers handling epoxy systems, in which ethylenediamine and related amines are used as curing agents , and in workers exposed to ethylenediamine‐containing coolant oils and synthetic coolants . Furthermore, allergic reactions to ethylenediamine have been reported in healthcare workers handling theophylline and aminophylline .…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis did not find an increased sensitization to EDD in health workers, probably as a result of the improvement of protective measures in this sector and the replacement of theophylline‐containing products with others, which are not dissolved in EDD 17 . In metallurgical engineering, OCD has been reported from EDD after exposure to coolant oils and lubricants, and even an epidemic occupational sensitization in a wire‐drawing factory has been described 22–25 . Among industrial and laundry detergents, there are a number of notable products that can contain EDD as bleach activator, 3 which may explain the sensitization observed in cleaners/domestics and also in hairdressers, as frequently performed the cleaning of the hairdressing salon 46 .…”
Section: Discussionmentioning
confidence: 65%
“…In industrial scenarios, OCD caused by EDD was described in metallurgical engineering after exposure to coolant oils 22,23 and lubricants 24,25 . English et al 26 reported a case of OCD, also to a floor polish remover in which the allergen was present.…”
Section: Introductionmentioning
confidence: 99%
“…A 48-h patch test to 5% Dichlorophene was positive, but not as severe as the two previous cases (Schorr 1970). Crow, Peachey, and Adams (1978) described the outbreak of dermatitis in 15 subjects in which eruptions affected the dorsal surfaces of the hands and fingers, which were dry, scaly, and erythematous with a tendency to fissure. One subject had eruptions on the palms and forearms.…”
Section: Case Reportsmentioning
confidence: 63%